Local wisdom as Humanity Education in the Legend of Lake Bagendit: A Sociolinguistic approach - Qoriah, Desi; Dioka Muhammad Akbar (IPI Garut Press, 2025)
Local wisdom in this modern life has been faded, overshadowed by the rapid pace of globalization and technological advancements. It is important to investigate humanity education embedded in cultural narratives, such as the Legend of Lake Bagendit, to preserve Humanity values and foster a sense of community. This study employs a descriptive qualitative method with a sociolinguistic approach to analyze the humanity dimensions reflected in the legend. Data were collected through textual analysis of the narrative, supported by interviews with cultural experts and a review of related literature to ensure triangulation. The findings reveal that the legend embodies key humanity values, very identic with “Nyi Endit” or Ms. Stingy so the values found are tolerance, respect and interconnected which are conveyed through symbolic language and social interactions within the story. These values are deeply rooted in Sundanese culture and serve as moral lessons that remain relevant to addressing contemporary social issues. This research emphasizes the significance of integrating local wisdom into modern educational frameworks to promote humanity education and cultural preservation.